An impedance investigation of corrosion protection of copper by self-assembled monolayers of alkanethiols in aqueous solution - SHENHAO CHEN; YONGLI JIAO; GUIYAN LI; HOUYI MA (Journal of the Serbian Chemical Society, 2004)
Self-assembled monolayers (SAMs) of three n-alkanethiols, 1-octadecanethiol (C18SH), 1-dodecanethiol (C12SH), and 1-hexanethiol (C6SH), were formed on fresh, oxide-free copper surfaces obtained by HNO3 etching. The corrosion protection abilities of the three alkanethiol SAMs were evaluated in 0.2 mol cm-3 NaCl, 0.2 mol cm-3 HCl and 0.2 mol dm-3 H2SO4 solutions using the electrochemical impedance spectroscopy (EIS) method. The SAMs act as a hydrophobic barrier layer, which effectively prevents the copper substrate from contacting corrosive ions, thereby inhibiting corrosion of the copper to a considerable degree. A general equivalent circuit for the SAM-covered electrodes was proposed, by means of which the impedance behavior of the electrodes was interpreted and the corresponding electrochemical parameters were acquired. In addition, the quality of the SAMs and development of defects in the SAMs were also been evaluated based on the equivalent circuit. The dependence of the capacitance of the SAMs on the applied potentials was used to determine the stability of the SAMs at the applied potentials.